Construction of Knowledge about Sholawat among "Bhenning" Recitation Members in Situbondo - Islamiyah, Shofiatul (Jurnal ENTITAS SOSIOLOGI, 2019)
This study explains the construction of knowledge among members of the Sholawat Bhenning Community in Situbondo. By using social construction theory, this research describes the reality of the community based on the experience of the Bhenning prayer members. The research method used was qualitative, with in-depth interviews toward members of Sholawat Bhenning. The results of this study are the participation of members in the prayer activities carried out by the Bhenning group has changed bad behavior into good behavior. Members have many reasons to join the Sholawat Bhenning community. 1) Members want to learn about theater; 2) Members were fascinated by Karisma Kyai Aza Ibrahimy, 3) Members wished to gain knowledge from the group of Sholawat Bhenning; 4) members wanted to get merit from Allah Subhanahu wata'ala. Finally, their participation was supported by their friends. Keywords: "Bhenning" prayer, Social Construction, youth, motivation involved, behavior change Referensi: Afifah, Latifatul. 2014. Eksistensi Pengajian Nurul Hidayat Dalam Meningkatkan Perilaku Sosial Keagamaan Remaja di Desa Trosono Kecamatan Sekaran Kabupaten Lamongan. Skripsi.UIN Sunan Ampel Surabaya Alfina, Citra 2017. Perilaku Beragama Masyarakat Urban di Kawasan Ampel Surabaya. Skripsi. UIN Sunan Ampel Surabaya Jayadina, Afnani 2012. Fungsi Sosial Pengajian Bergilir di Rumah Warga.Jurnal Penelitian.Yogyakarta Handayani E, Motivasi Ibu-ibu Rumah tangga mengikuti pengajian muslimat NU di ranting Troso Kecamatan Karanganom Kabupaten Klaten. Jurnal Skripsi.Yogyakata Ismaya DT, 2010. Akulturasi Budaya Hindu dan Islam dalam Cerita Perwayangan. Skripsi : Universitas Negeri Islam sunan Kalijaga Yogyakarta Demartoto A.2013. Teori Konstruksi Sosial Dari Peter L Berger dan Thomas Luckman http://argyo.staff.uns.ac.id/2013/04/10/te ori-konstruksi-sosial-dari-peter-l-berger- dan-thomas-luckman/ (diakses pada 19 September 2018 jam 23.00) Noviani N. 2015. Wali Songo dalam mempengaruhi Budaya Nusantara https://nuniknoviani.wordpress.com/201 5/05/19/wali-songo-dalam- mempengaruhi-budaya- nusantara/.(diakses pada 06 Oktober jam 21.34)